Beyond patient culture: filtering cultural presentations of depression through structural terms - Brijnath, Bianca; Antoniades, J. (Routledge, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group There is growing global consensus for researchers to look beyond patient culture to gain a more nuanced understanding of the ways in which wider socio-structural forces influence health outcomes. In line with these critiques, this paper examines culturally diverse patients’ views about the symptoms, aetiology, and experiences of their depression, and considers how socio-structural forces are implicated in the illness experience. Analysing the transcripts of interviews with 28 Indian-Australians and 30 Anglo-Australians with depression, our results reveal cultural differences between Indian- and Anglo-Australians regarding the chronicity, perceived severity, and aetiology of their depression. Our results also show how these cultural differences are related to socio-structural forces such as time, money, and migration. We conclude by arguing that the current medicalised approach to treating depression needs to shift to a more empathetic problem-solving one; such a change would prompt greater critical consideration of the socio-structural forces that impact people’s mental health and not just focus on individuals’ culture and pathologies.